Study of copper removal from liquid iron - J. Łabaj; B. Oleksiak; G. Siwiec (Metalurgija, 2011)
The technology of steel is projected to increase in the share-based processes for processing recyclable materials. On the one hand it creates the possibility of lowering the cost of producing steel, while the other is causing the pollution, which because of its physicochemical properties are difficult to remove. The group of this type of pollution is classified as copper. The lower reactivity to iron requiring the analysis of thermodynamic parameters of Fe-Cu system to identify how best to allocate them. The study was conducted for the basic kinetic analysis of Fe-Cu alloy containing 0,5 % wt. Cu and 1,5 % wt. Cu in the pressure range from 0,06 to 1 074 Pa and a temperature of 1 923 K The study was conducted in a vacuum induction furnace VIM-20-50 Seco Warwic.